Microstructure and dielectric properties of nickel-doped Ba0.7Sr0.3TiO3 ceramics fabricated by solgel method - Kakumani, Asa Deepthi; Ruthramurthy, Balachandran; Wong, Hin Yong; Ong, Boon Hoong; Tan, Kar Ban; Yow, Ho Kwang (The American Ceramic Society, 2016)
A study of phase transition, microstructure, and dielectric properties of Ba0.7Sr0.3Ti1–xNixO3 (BSTN) ceramics prepared by slow-injection solgel technique with x ranging from 0 to 1 mol% is reported in this article. The as-prepared BSTN material was calcined at 800 and 1000°C and subsequently sintered at 1100 and 1200°C, respectively. The optimized condition was found to be Ba0.7Sr0.3TiO3 doped with 1 mol% nickel calcined at 1000°C and sintered at 1200°C having the lowest dielectric loss of 0.02 with a dielectric constant of 1603 which was measured at a frequency of 1 kHz at room temperature.